Comprehensive review on graphene, its synthesis, properties and applications in drug delivery - Md. Shalauddin, (Malaysian NANO-An International Journal, 2024)
Graphene, a single layer of carbon atoms arranged in a two-dimensional honeycomb lattice, has garnered significant attention for its exceptional properties and versatile applications. This comprehensive review delves into the synthesis, properties, and burgeoning applications of graphene in drug delivery systems. We explore various synthesis methods, including mechanical exfoliation, chemical vapour deposition, and reduction of graphene oxide, highlighting their advantages and limitations. The review discusses graphene's remarkable mechanical strength, electrical conductivity, thermal stability, and large surface area, which contribute to its efficacy as a drug delivery platform. Furthermore, we examine the biocompatibility and functionalization strategies that enable targeted and controlled drug release. Applications in cancer therapy, gene delivery, and tissue engineering are scrutinized, demonstrating graphene's potential to revolutionize these fields. Challenges such as toxicity, scalability, and regulatory considerations are also addressed, providing a balanced perspective on the future of graphene in biomedical applications. This review aims to provide a comprehensive understanding of graphene's role in drug delivery, paving the way for further research and development in this promising area.